Long-short speculator sentiment in agricultural commodity markets - Oliver Borgards; Robert L. Czudaj (Chemnitz University of Technology, Faculty of Economics and Business Administration, 2022)
This paper tests the hypothesis that long-short speculators are able to generate short-term investment returns based on their sentiment for twelve agricultural commodity futures. For this purpose, we dynamically model the equidirectional trading of long and short commodity futures of long-short speculators as a proxy for their market sentiment. We find evidence that the sentiment period returns are considerably positive and differ significantly from neutral sentiment periods for all commodities which underlines the sentiment's relevance. In line with the empirical literature, we can reject the argument of price manipulation as the price continues to develop into the direction of the sentiment period although long-short speculators trade non-directionally in the following. We rather indicate the existence of a short-term time-series momentum effect, which can be robustly identified without the requirement to define an external model parameter. From the superior sentiment-based momentum returns, we conclude that long-short speculators have valuable, exclusive information, which cannot be replicated by observing their trading activity with a time lag of eight trading days. We also find that a sentiment-based momentum strategy generates significantly higher returns than the long-short speculators have realized in the fifteen-year sample period which we attribute to the complexity of the long-short speculators' investment strategies.
Keywords: G11; G14; G15; C18; 330; commodities; time-series momentum; sentiment; long-short speculators; commitment of traders; price manipulation